KEBIJAKAN OTONOMI DESA DALAM PENGELOLAAN KEUANGAN DESA DI DESA WAYALOAR SATU KECAMATAN WAYALOAR KABUPATEN HALMAHERA SELATAN - Kajual, Justina Anjelia; Pangkey, Masje Silija; Rompas, Sonny (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract Birth of Law Number 32 Year 2004 on Regional Government in which regions have theauthority to make policy in the village to provide services, increased participation and empowerment asstated in Law No. 32 Year 2004 on Regional Government. Embodiments of village autonomy is a process ofimproving the ability of people to participate to the public life with the principles of, by and for thecommunity.This study aimed to: determine the extent of village autonomy in financial management in the ruralvillages of the districts wayaloar wayaloar Halmahera district south. This study is trying to see the truth andhave to trace it farther something tangible as a qualitative method. Data used in this study to encompassprimary data obtained from the village government, chairman / deputy, secretary and treasurer or otheradministrators who will be in the interview.Results of this research is expected to provide sumbangsi to science especially the social sciences inparticular disciplines of public administration policies village autonomy in the management of villagefinances and also to contribute ideas for policy makers especially village government wayaloar one districtwayaloar Halmahera district south in management of village finances.Keyword :village autonomy policy, management, finance